Acute sleep deprivation is associated with increased arterial stiffness in healthy young adults - SARI, İBRAHİM; SÜNBÜL, MURAT (SPRINGER HEIDELBERG, 2014)
Background Arterial stiffness and its hemodynamic consequences are known to be associated with increased cardiovascular morbidity and mortality. Pulse wave velocity (PWV) and augmentation index (AIx) are noninvasive indicators of the arterial stiffness and wave reflection. Sleep deprivation (SD) is known to be associated with increased incidence of adverse cardiovascular events. The aim of this study was to investigate whether there is an association between acute SD and arterial stiffness parameters in healthy adults, which has not been studied previously. Methods The study population consisted of 42 healthy volunteers (18 males, mean age 30.0 +/- 4.5 years). Measurements of arterial stiffness were carried out by using a Mobil-O-Graph arteriograph system. Arterial stiffness measurements were obtained both after a night with regular sleep (RS) and after a night with SD. Results Mean sleep time was significantly lower after the night of SD when compared after RS (0.73 +/- 1.39 versus 7.33 +/- 0.52 h, p < 0.001). Peripheral systolic blood pressure, peripheral pulse pressure, and cardiac output were significantly higher after SD when compared after RS (p = 0.032, 0.007, and 0.003, respectively). PWVwas significantly higher (5.33 +/- 0.46 versus 5.15 +/- 0.26 m/s, p = 0.001), and AIx was significantly lower (20.5 +/- 11.9 versus 26.0 +/- 8.4 %, p = 0.008) after the night of SD when compared after the RS. While PWV was significantly higher (p= 0.008), and AIx was significantly lower (p = 0.039) in male subjects, only PWVwas significantly higher (p = 0.009) in female subjects. Sleep time correlated with AIx (p = 0.034; r = 0.233) and inversely correlated with PWV (p = 0.044; r = -0.222). Conclusion In the present study, we demonstrated that even one night of SD is associated with increased arterial stiffness in healthy adults. The present findings suggest that adverse effects of SD on cardiovascular system might be at least in part due to increased arterial stiffness which needs to be tested with large-scale studies and in the chronic SD setting.
Keywords: Sleep deprivation; Arterial stiffness; Healthy adult; Cardiovascular risk; BLOOD-PRESSURE; TASK-FORCE; ENDOTHELIAL FUNCTION; CARDIOVASCULAR RISK; BRACHIAL-ARTERY; DURATION; INSOMNIA; HYPERTENSION; MORTALITY; ATHEROSCLEROSIS